Midwifery Care for Mrs. K's Baby with Abdominal Bloating Using Telon Oil - Nofita Tri Lestari; Diah Atmarina Y; Sawitri Dewi (Proceedings Series on Health & Medical Sciences, 2021)
Bloating (meteorism, tympanities) is a symptom that indicates the presence of air or gas in the abdominal or intestinal cavity (Gina et al., 2020). In newborns (neonates) occurs because the digestive system in neonates is immature, besides that there are not enough digestive enzymes available at birth, and will only reach sufficient levels with increasing age, this is as stated by Padila et al. , 2019. To overcome flatulence in infants, non-pharmacological therapy can be used, namely by using telon oil by massaging it on the baby's stomach, this can reduce bloating in infants. To determine the application of telon oil to reduce bloating in new born. Case study report using descriptive method, the location of the residence of Mrs. K in Nangkod Village Rt02/05, Kejobong District, Purbalingga Regency. The subject of the case study was a 15-day-old newborn with flatulence. Time of case study on 9 April 2021. Data collection techniques include interviews and secondary studies including documentation and literature studies. The general condition of the new born is good, after massaging using telon oil the baby fart. Giving massage using telon oil is effective for reducing flatulence in babies.